Optimal Design for Frequency Fluctuation Control System with SMES Unit - Xuan Khoa Tran; Y. Chen; G. T. Phan; D. H. Huynh (My University, 2020)
Optimal Design for Frequency Fluctuation Control System with SMES Unit
Keywords: Tần số hệ thống điện; SMES Unit; Tối ưu hóa thiết kế